Abstract 011: Endovascular therapy for acute ischemic stroke utilizing SOFia Aspiration System as first line Technique (SOFAST) - Dheeraj Gandhi; Daniel Sahlein; Syed Zaidi; Lucian Maidan; Kenneth Kreitel; Timothy Miller; Scott Rahimi; Amer Alshekhlee; Henry Woo; Gabor Toth; Clemens Schirmer; Vince Loh; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Mechanical thrombectomy using stent retrievers and aspiration techniques has emerged as the standard of care for patients with acute ischemic stroke (AIS) secondary to emergent large vessel occlusion (LVO). This study intended to collect real‐world clinical evidence on the safety and effectiveness of endovascular treatment of AIS using the SOFIA Flow Plus 6F aspiration catheter. The primary endpoint was the proportion of subjects achieving mTICI ≥2b. Secondary endpoints included good functional outcomes (mRS 0‐2) at Day 90, revascularization time, first line and first pass mTICI ≥2b, occurrence of procedure‐related SAEs, vasospasm involving the accessed vascular tree, embolization to new territories (ENTs), symptomatic intracerebral hemorrhage (sICH) within 24 hours and mortality at Day 90. Methods SOFAST was a prospective, multicenter, single‐arm, observational post‐market study. The enrolled subjects were ≥21 and ≤85 years with large vessel (ICA or MCA) proximal occlusion, pre‐morbid mRS ≤1, baseline NIHSS ≥5, and for whom groin puncture was within 8 hours of symptom onset. A total of 108 patients were enrolled and treated using aspiration thrombectomy with SOFIA 6F as the first line treatment device. Patients were followed at 24 hours, 7 days/discharge, and 90 days post‐procedure. Cerebral angiography was performed pre‐ and post‐procedure. Clinical assessments included the NIHSS and mRS scales. All neurological, device‐related, and procedure‐related AEs and deaths were adjudicated by independent medical reviewers. Angiographic and other imaging data was adjudicated by an independent core laboratory. Results A total of 108 subjects were enrolled (mean age 62.7 years, 50% men) with a median NIHSS of 15.5. Of 108 subjects, 97.2% (105/108), 85.2% (92/108) and 55.6% (60/108) achieved mTICI ≥2b, ≥2c and =3 revascularization, respectively. With first line aspiration using SOFIA 6F, 87.0%, 79.6% and 52.8% achieved mTICI ≥2b, ≥2c and =3 revascularization, respectively. Median number of passes was one (range 1‐3). First pass rate of mTICI 2c or 3 using SOFIA 6F was 70.4%, of which 50.9% patients achieved mTICI score of 3. Mean duration from groin puncture to initial clot contact was 13.0 min and to successful revascularization was 17.9 min. Good functional outcome was achieved in 66.7% (72/108) of subjects at Day 90 (mRS 0‐2), procedure‐related SAEs occurred in 2.8% (3/108) of subjects and sICH in 0.9% (1/108) of subjects within 24 hours. Procedural vasospasm was recorded in in 9.3% (10/108) of subjects, and mortality in 7.4% (8/108) subjects at Day 90 (none related to the study device). No ENTs occurred. Conclusion In SOFAST study, mTICI ≥2b revascularization was achieved in the majority of patients at the end of all procedures (97.2%) and with first line treatment (87.0%) with a large fraction of these subjects achieving mTICI ≥2c following the first SOFIA 6F pass (70.4%). Durations from groin puncture to clot contact and successful revascularization were relatively short. The study presented high rates of good functional outcome at Day 90 and low rates of safety events. In summary, the study provides encouraging evidence of the safety and effectiveness of the SOFIA 6F device for aspiration thrombectomy in acute ischemic stroke subjects.